(untitled) (Medical Forum Monthly, 2023)
Objective: To study the effect of short-term use of injectable DMPA for contraception in immediate postpartum women. Study Design: A prospective cohort study Place and Duration of Study: This study was conducted at the Department of Obstetrics and Gynecology Lady Reading Hospital, Peshawar for duration of six months from 02-June 2022 to 02- December 2022. Materials and Methods: A total of 100 females were enrolled by using a purposive sampling technique. Depot medroxyprogesterone acetate (DMPA) intramuscular 150 mg injections were administered from day 2 to 10 of the delivery, after their baseline assessment which was normal. All these women were followed for a period of six months with a proper gap of three months. Every three months they were properly assessed in terms of bleeding irregularities, haemoglobin level, bilirubin level, and the side effect of the DMPA. The data were analyzed by using the latest version of SPSS. Results: There was a mild bleeding irregularity in 16 % at first assessment, 39 % after the time of three months, and 41 % after the time of six months. Moreover, 10 % of the females had a moderate irregularity in bleeding at the initial assessment, 30 % after three months of time, and 21 % after the time of six months. During the first three months, 14 % of cases had developed gain of Weight, and it was reduced to 11 % after the time of six months. Consequently, 09 % and 08% of the cases had experienced backache and headache in the first three months; however, this was reduced to 07 % and 04 % after the time of six months. Conclusion: The study shows that DMPA is one of the easy and highly effective methods for family planning purposes and for those females who wants to delay their pregnancy. After the effect of DMPA pregnancy is completely reversible. Though there are some side effects of DMPA, it is manageable and does not put the life of females at risk.